(untitled) (NTU Journal of Agriculture and Veterinary Science, 2024)
The experiment was conducted in the fields of the College of Agriculture and Forestry University of Mosul for the autumn season 2022-2023, and Ten genotypes were used, namely (DR-F-53, MA-F-53, H-4, DKC-F-59, IK-58, ZP-595, POL-F-6, SYM-F-53, MY-F-53 and SYN-F-54) To study the genetic stability of genotypes of maize according and the experiment was a The Randomized Complete Block Design (R.C.B.D) was used with three replicates and the traits of studied (date of tasseling , date of silking , number of ears per plant , number of grains per ear , weight of 500 grains, single plant production) . The results showed that in terms of genetic, phenotypic and environmental variations, heritability in the broad sense, and the expected genetic improvement as a percentage, it was high for all genotypes and for all traits, and this gives an opportunity for selection for these superior traits.